Optimization Research and Exploration of New Rural Cooperative Medical Information System - Zhang, Guohua (International Journal of Online and Biomedical Engineering (iJOE), 2021)
<span style="line-height: 114%; letter-spacing: 0.1pt; font-family: ’Times’,’serif’; font-size: 10pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 宋体; mso-bidi-font-family: ’Times New Roman’; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">The New Rural Cooperative Medical Care Information System (NRCMS) used a single relational database to store most of the data in the early days. The scheme is difficult to expand and has little concurrent ability, so it is not suitable to deal with semi-structured, Unstructured data. Then along came distributed technologies such as Hadoop, which had the advantage of using inexpensive machines to store and process data. But HADOOP was designed to distribute data equally among the nodes in the cluster for storage and processing, ignoring the differences in the storage and computing capabilities of the cluster nodes themselves, and the performance of individual nodes even affects the performance of the collation system, and it is master-slave node processing data, there are data can tamper, system terminal is too single and so on. The contribution of this paper lies in the overall structure and technical route of the new rural cooperative medical system, and the optimization method of data flow of heterogeneous nodes, which can effectively save the scale and cost of the cluster, with the help of blockchain technology to ensure the security and credibility of data, optimize the front-end cluster service architecture, support multi-channel and high-concurrent key information push mode, has a very good promotion.